Incidence Des Fortes Fréquences De Stimulation Hormonale Sur Deux Régimes de Saignée Descendante Du Clone PB 215 : Faible (d6) et Modéré (d4), Au Sud-Est De La Côte D’Ivoire - Coulibaly Lacina Fanlégué; Traoré Mohamed Sahabane; Kouamé N’dri Marie-Thérèse (European Scientific Journal, ESJ, 2018)
The clone PB 235 of Hevea brasiliensis is characterized by a rapid growth, homogeneity, and a virgin bark which is suitable for tapping. However, it is sensitive to the very intense latex systems harvesting technologies. This paper focuses on determining the incidence of strong frequencies of stimulation on two downward tapping systems of clone PB 215: low (d6) or moderate (d4). Rubber trees were planted with the density of 510 trees/ha (7 m x 2.8 m) in accordance with a randomized complete block design. Tapping at d6 frequency with 8 and 12 hormonal stimulations and the d4 stimulated 0 and 8 times per year were evaluated. The intensification of hormonal stimulation with the d6 did not have any worthy beneficial effect on the dry rubber yield of the rubber trees. In d4, the stimulation involved a reduction in the sucrose content which led to a significant increase of the dry rubber yield. However, it contributed to an increase in the tapping panel dryness. At moderate tapping, the application of hormonalstimulation allowed us to distinguish between the two latex harvesting technologies. At d6, the two treatments were similar regardless of the stimulation level. Tapping at d6 supports a reduction of tapping workforce and a longer economical durability of the trees, compared to tapping at d4. The intensification of hormonal stimulation applied to lower tapping frequencies (d6) did not have any negative incidence on the clone PB 235. However, it has promoted tapping panel dryness in tapping at d4 frequency.